2019
DOI: 10.2215/cjn.02050219
|View full text |Cite
|
Sign up to set email alerts
|

Shared Hemodialysis Care

Abstract: Reann's story "When I first heard that I could share doing some of my own hemodialysis, I was scared and thought I could never do that! Despite my initial fear, I have learned how to needle. I found this rewarding and now I am in control. I have a lot less issues with my fistula now and I can get on with my dialysis without waiting for the nursing staff." Nicholas' story "Shared Care means a better way of life for me and my family. It has given me understanding so that I know what is happening during my dialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…There is already evidence that patient education is associated with better patient outcomes 59 and new strategies and quality improvement programmes exist such as Shared HD, a UK programme aiming to support patients receiving in-centre HD to be more independent and confident in participating in aspects of their own care. 60 Potential barriers are cost and resources, but increasingly, accredited online learning facilities are available. However, it is acknowledged, staff in this study indicated a preference for face-to-face training.…”
Section: Discussionmentioning
confidence: 99%
“…There is already evidence that patient education is associated with better patient outcomes 59 and new strategies and quality improvement programmes exist such as Shared HD, a UK programme aiming to support patients receiving in-centre HD to be more independent and confident in participating in aspects of their own care. 60 Potential barriers are cost and resources, but increasingly, accredited online learning facilities are available. However, it is acknowledged, staff in this study indicated a preference for face-to-face training.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low activation are highrisk patients in need for more surveillance and need an integrated approach to improve their activation. To influence a meaningful and sustainable change in dialysis care that improves patient activation, we will need an integrated approach that involves people on dialysis, their healthcare team, dialysis providers, and policy makers (48,49). Interventions that can be considered include health coaching, peer mentoring, and involving patients more in their dialysis care (50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…31 These approaches can be enhanced by leveraging technology (telehealth), increasing patient's access to their own health records and measures such as patient reported outcomes. 27 These interventions have resulted in increased engagement 32 and confidence, reduced anxiety, 31 improved clinical outcomes, 30,33 improved patient-reported quality of life, 34 satisfaction with care, 35 increased satisfaction with modality decision making, 36 and potentially increased number of patients moving to home dialysis. 31 The ultimate goal of our early dialysis care would be to increase a person's activation by increasing their knowledge, skills, and confidence so that they are able to manage their own health and health care.…”
Section: Discussionmentioning
confidence: 99%
“…27 These interventions have resulted in increased engagement 32 and confidence, reduced anxiety, 31 improved clinical outcomes, 30,33 improved patient-reported quality of life, 34 satisfaction with care, 35 increased satisfaction with modality decision making, 36 and potentially increased number of patients moving to home dialysis. 31 The ultimate goal of our early dialysis care would be to increase a person's activation by increasing their knowledge, skills, and confidence so that they are able to manage their own health and health care. The expected improvements in healthy behaviors and ownership of one's health care is the essence of person-centered care, and will support the transition to value-based care and the achievement of the quadruple aim: better patient outcomes; improved clinical experience; improved patient experience; and lower costs.…”
Section: Discussionmentioning
confidence: 99%